ONLINE FLIPPED CLASSROOM (e-FCR): WAY FORWARD IN COVID 19 ERA - Babar, Shazia; Hidayat, Mariyah (Journal of Ayub Medical College Abbottabad, 2022)
Online teaching and learning have been in place for the last two decades. COVID-19 pandemic has intensely augmented institutions towards implementation of online teaching. Literature reported benefits of online learning including flexibility and self-direction. In addition, researchers reported that virtual learning pedagogy is encouraging, as it mainly inspires lifelong learning due to its self-paced and self-directed instruction. Flipped classroom is an active pedagogical instructional strategy that uses online resources external to the classroom, and then employs small group pedagogies within the classroom. Flipped classroom strategy allows use of lecture time for active learning activities. This active model restructures the traditional lecture paradigm, in that students acquire basic course content before coming to the classroom, while class time is dedicated for problem solving learning activities. Flipped classroom utilizes time in student interaction sometimes one to one, addressing to their concerns and queries regarding the content. This strategy gives opportunity to the teachers to share their relevant real-life experiences and design small group problem solving activities.